Repellent Action Of Neem (Azadiracta India) Seed Oil Against Aedes Aegypti Mosquitoes - Hati A K; Bhowmik Keya; Banerjee A; Mukherjee H; Poddar G; Basu D; Dhara K P (Wolters Kluwer Medknow Publications, 1995)
Neem (Azadiracta India) seed oil in appropriate amount when smeared on the surface of the hand showed excellent repellent action against Aedes aegypti mosquitoes. When 1 ml of oil was spread on the hand, with an approximate area of 160 sq cm the percentage of alighting and blood fed mosquitoes in the experimental cages varied from 14 to 78 and 4 to 46 respectively. This percentage decreased to 6 to 18 and 0 to 16 respectively when the amount of oil applied was 1.5 ml. Only 0-4% of the mosquitoes alighted on the skin of which 2% only took the blood meal when 2 ml of the oil was used to cover the hand. In the control cages cent percent of the mosquitoes alighted and sucked blood. The repellent action was directly proportional to the hour of exposure to the oil. It was also observed that even after alighting on a oil- smeared skin a sizeable proportion of mosquitoes were not able to imbibe blood meal. Neem seed oil was non-toxic, non- irritating to skin.